DIPG-29. PRECLINICAL EFFICACY OF COMBINED ACVR1 AND PI3K/mTOR INHIBITION IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). Issue 2 (22nd June 2018) - Carvalho, Diana; Olaciregui, Nagore Gene; Ruddle, Ruth; Donovan, Adam; Pal, Akos; Raynaud, Florence; Richardson, Peter J; Carcaboso, Angel Montero; Jones, Chris
Abstract: Somatic mutations in ACVR1, encoding the serine/threonine kinase ALK2 receptor, are found in a quarter of DIPG patients. Treatment of ACVR1 -mutant DIPG patient-derived models with multiple ALK2 inhibitor chemotypes leads to a reduction in cell viability in vitro and extended survival in orthotopic xenografts in vivo, though as monotherapies they are not sufficient to achieve complete anti-tumour response. As alterations in the PI3-kinase pathway (PIK3CA, PIK3R1, PTEN) co-segregate with ACVR1 mutations in patient samples, we sought to explore the utility of combinatorial targeting of ALK2 and PI3K/mTOR. Two orally bioavailable ALK2 inhibitors with good CNS penetration (LDN-193189, LDN-214117) showed synergy with the mTOR inhibitors AZD8055 and everolimus in a series of patient-derived DIPG cells in vitro, though these molecules remain lead compounds and not clinically-approved drugs. In an Artifical Intelligence-augmented search for approved compounds which could be used to treat DIPG, the combination of vandetanib and everolimus was identified as a possible therapeutic approach. Vandetanib, an approved inhibitor of VEGFR/RET/EGFR, was found to target ALK2 (Kd=150nM) and reduce DIPG cell viability in vitro, but has been trialed in DIPG patients with limited success, in part due to an inability to cross the blood-brain-barrier. In addition to mTOR, everolimus inhibits the ABCG2 and P-gp transporters, and was synergistic in DIPG cells when combined with vandetanib in vitro . This combination is well-tolerated in vivo, results in micromolar levels of vandetanib in the mouse brain, and is shown to effectively inhibit pharmacodynamic biomarkers. This may represent a rapidly translatable approach in children with ACVR1 mutant DIPG.